Strategi Pembiayaan Berkelanjutan dalam Penyediaan Perumahan Layak Huni Bagi Masyarakat Berpenghasilan Rendah: Sebuah Analisis Bibliometrik - Andek Prabowo; Ika Sartika (JOM, 2025)
This study discusses the bibliometric analysis of financing for the provision of housing for low-income communities (MBR) in the Jabodetabekpunjur agglomeration area, with a focus on the development of a sustainable financing structure involving synergy between the central government, regional governments, state-owned enterprises, the private sector, and international institutions. The analysis shows that areas such as Jabodetabekpunjur face a significant housing backlog due to rapid urbanization and population growth, so innovations such as endowment-based financing schemes, flexible subsidies, and cross-sector collaboration are needed. The strategies include simplifying bureaucracy, optimizing land assets, strengthening coordination between agencies, and involving local governments and CSR in housing provision. Programs such as the Indonesia Green Affordable Housing Program (IGAHP) also propose to support environmentally friendly financing. This study provides policy recommendations and innovation strategies to achieve the target of building three million inclusive and sustainable livable homes.